The Use of Plotagon-Based Video Dialogue Media to Improve Arabic Speaking Skills - Niswatul Izzah; Saefullah Azhari; Ahmad Mudzakkir Hasyim (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2026)
This study aims to examine the effect of using Plotagon-based video dialogue media on improving students’ Arabic speaking skills (maharah kalam) at grade XI-10 of MAN Sidoarjo. This research employed a quantitative approach with a pre-experimental one-group pretest–posttest design. The research subjects consisted of 38 students. Data were collected through speaking skill tests, observation, and documentation. The speaking skill assessment instrument covered pronunciation, speaking intonation, fluency, vocabulary, and grammatical accuracy. Data were analyzed using the Wilcoxon Signed Rank Test due to non-normal data distribution. The results showed an increase in the students’ average speaking scores from 74 in the pretest to 87 in the posttest. The Wilcoxon test indicated a significant difference between students’ speaking abilities before and after the treatment, with a significance value of 0.000. Furthermore, the effect size calculation yielded an r value of 0.87, which falls into the large effect category. Therefore, it can be concluded that Plotagon-based video dialogue media is effective and has a significant impact on improving students’ Arabic speaking skills.